(untitled) - G A Taylor (London, 1993)
The book presents the chemical aspects of life processes. Early chapters of the book are concerned with developing organic chemistry from first principles, commencing with atomic and molecular structure and leading on the descriptive chemistry of monofunctional compounds; emphasis throughout is on a mechanistic interpretation of reactions. A description of the chemistry of selected polyfunctional compounds the moves on to introduce more complex molecules of obvious biological importance. The principles of stereochemistry are outline, and their importance is illustrated in the context of both general organic chemistry and cell reactions. A final chapter, concerned with a few selected groups of compounds of medical significance, introduces the relationship between the structure and shape of molecules and their physiological activity
Keywords: chemistry, organic